Selective reconstitution of IFN‑γ gene function in Ncr1+ NK cells is sufficient to control systemic vaccinia virus infection - Borst, Katharina; Flindt, Sven; Blank, Patrick; Larsen, Pia-Katharina; Chhatbar, Chintan; Skerra, Jennifer; Spanier, Julia; Hirche, Christoph; König, Martin; Alanentalo, Tomas; Hafner, Martin; Waibler, Zoe; et al. (PLoS pathogens, 2020)
IFN-γ is an enigmatic cytokine that shows direct anti-viral effects, confers upregulation of MHC-II and other components relevant for antigen presentation, and that adjusts the composition and balance of complex cytokine responses. It is produced during immune responses by innate as well as adaptive immune cells and can critically affect the course and outcome of infectious diseases, autoimmunity, and cancer. To selectively analyze the function of innate immune cell-derived IFN-γ, we generated conditional IFN-γOFF mice, in which endogenous IFN-γ expression is disrupted by a loxP flanked gene trap cassette inserted into the first intron of the IFN-γ gene. IFN-γOFF mice were intercrossed with Ncr1-Cre or CD4-Cre mice that express Cre mainly in NK cells (IFN-γNcr1-ON mice) or T cells (IFN-γCD4-ON mice), respectively. Rosa26RFP reporter mice intercrossed with Ncr1-Cre mice showed selective RFP expression in more than 80% of the NK cells, while upon intercrossing with CD4-Cre mice abundant RFP expression was detected in T cells, but also to a minor extent in other immune cell subsets. Previous studies showed that IFN-γ expression is needed to promote survival of vaccinia virus (VACV) infection. Interestingly, during VACV infection of wild type and IFN-γCD4-ON mice two waves of serum IFN-γ were induced that peaked on day 1 and day 3/4 after infection. Similarly, VACV infected IFN-γNcr1-ON mice mounted two waves of IFN-γ responses, of which the first one was moderately and the second one profoundly reduced when compared with WT mice. Furthermore, IFN-γNcr1-ON as well as IFN-γCD4-ON mice survived VACV infection, whereas IFN-γOFF mice did not. As expected, ex vivo analysis of splenocytes derived from VACV infected IFN-γNcr1-ON mice showed IFN-γ expression in NK cells, but not T cells, whereas IFN-γOFF mice showed IFN-γ expression neither in NK cells nor T cells. VACV infected IFN-γNcr1-ON mice mounted normal cytokine responses, restored neutrophil accumulation, and showed normal myeloid cell distribution in blood and spleen. Additionally, in these mice normal MHC-II expression was detected on peripheral macrophages, whereas IFN-γOFF mice did not show MHC-II expression on such cells. In conclusion, upon VACV infection Ncr1 positive cells including NK cells mount two waves of early IFN-γ responses that are sufficient to promote the induction of protective anti-viral immunity.